Novel Bio-Markers for Prediction of Preeclampsia - Garg, Ruchika; Singh, S; Dhiman, S; Agrawal, P; Prakash, P (Nepal Journal of Obstetrics and Gynaecology, 2016)
Pre-eclampsia (PE) is a pregnancy related disorder. It is an important cause of maternal and perinatal morbidity and mortality worldwide. Two to eight percent of pregnancies were affected by PE. It is characterized by de novo hypertension and proteinuria after 20 weeks of gestation. The etiology and pathogenesis of the disease is unknown, but recent studies have revealed that placenta is the place of origin of this disorder and widespread maternal endothelial dysfunction is the characteristic feature of the disease. Some biochemical molecules are identified recently which are involved in the pathogenesis of the disease, which may help in early identification of patients at risk and help in providing proper prenatal care. Several promising biomarkers have been proposed, alone or in combination. Maternal serum concentrations of these biomarkers either increase or decrease in PE during gestation. This review focuses on the various biomarkers available and their utility in prediction and diagnosis of pre-eclampsia.